Draft Annual Plan 1986-87 Volume VII Industries and Commerce Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
The 7th Plan proposals had earlier been drawn with a total investment of Rs, 1730 lakhs of which the equity component was Rs. 560 lakhs and the term loan Rs. 1110 lakhs. The Company formulated these proposals with a view to diversify, the production lines,. Continuing with the traditional lines for long. can adversely effect the operational viability of the Company in future. The Company on its own is not in a position to invest cash surpluses generated so far as the same remain blocked in inventories.
Planning and Development Department, Jammu and Kashmir Government